2019
DOI: 10.3390/ijms20184468
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Framework to Probe the Binding Hypothesis of CYP3A4 Inhibitors

Abstract: The Cytochrome P450 family of heme-containing proteins plays a major role in catalyzing phase I metabolic reactions, and the CYP3A4 subtype is responsible for the metabolism of many currently marketed drugs. Additionally, CYP3A4 has an inherent affinity for a broad spectrum of structurally diverse chemical entities, often leading to drug–drug interactions mediated by the inhibition or induction of the metabolic enzyme. The current study explores the binding of selected highly efficient CYP3A4 inhibitors by doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 106 publications
1
13
0
Order By: Relevance
“…The wild-type pocket volume range of CYP3A5 calculated in our study confirmed such property. Our results also show higher pocket volume values reported previously for CYP3A4 evaluated to 1386 Å 3 and 520 Å 3 from two different studies [36]. These values, however, were reported based on single-point calculations for the unbound structure of CYP3A4.…”
Section: Catalytic Pocket Volume Calculationsupporting
confidence: 69%
“…The wild-type pocket volume range of CYP3A5 calculated in our study confirmed such property. Our results also show higher pocket volume values reported previously for CYP3A4 evaluated to 1386 Å 3 and 520 Å 3 from two different studies [36]. These values, however, were reported based on single-point calculations for the unbound structure of CYP3A4.…”
Section: Catalytic Pocket Volume Calculationsupporting
confidence: 69%
“…Morever, calpain inhibitors and GC-376 analogs are also confirmed to accommodate in the same functional pocket [ 58 ]. Beside these, many in silico studies have demonstrated the binding affinity of drug molecules to this active side of Mpro [ 33 , 59 , 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The involvement of serine here is not unexpected as the implicated iminium ion species is a hard electrophile and will preferentially react with a nucleophile of comparable 'hardness' such as the hydroxyl groups of serine residues (LoPachin and DeCaprio, 2005). Additionally, the possibility of this serine residue being implicated in its MBI is further reinforced by a recent study which identified Ser312 in CYP3A4 as an important binding site residue implicated in ligand inhibitory interactions (Kiani et al, 2019).…”
Section: Discussionmentioning
confidence: 74%